Maxims of experience in the rational assessment of evidence: Proper and improper use from a gender perspective - Limay Chavez, Raquel (2021)
The present paper intends a doctrinal, legal and jurisprudentially analysis of the so-called maxims of experience in the assessment of evidence from two perspectives: rational or epistemological and gender perspective. Both approaches are relevant because the first approach conceives the maxims of experience as assessment criterion and empirical generalizations with conditional form, susceptible to be classified as true or false if it does not correspond to an empirical verification. The second point of view, will allow showing the improper interpretation and application of these assessment criterion as arguments based on of biases and gender stereotypes, mainly, in sexual crimes, and that are hidden under the denomination of maxims of experience of the judge, this directly affects the rational assessment of evidence making this a simply subjective appreciation.